If u=`f((y-x)/(xy),(z-x)/(xz)),"show that" x^2 (del_u)/(del_x)+y^2 (del_u)/(del_y)+x^2 del_u/del_z=0`

Advertisement Remove all ads

#### Solution

Let u=f(r,s)

∴` r=( y-x)/(xy)` ∴ `s=(z-x)/(xz)`

∴ `del_u/del_x=(del_u del_r)/(del_r del_x)+(del_u del_s)/(del_s del_x)=(del_u 1)/(del_r x^2)+del_u/del_s((-1)/x^2)`

`del_u/del_y=(del_u del_r)/(del_r del_x)+(del_u del_s)/(del_s del_y)=del_(-1)/(del_r y^2)+del_u/del_s(0)`

`del_u/del_z=(del_u del_r)/(del_r del_z)+(del_u del_s)/(del_s del_z)=del_u/del_r(0)+del_u/del_s(1/z^2)`

∴ `x^2 del_u/del_x+y^2 del_u/del_y+z^2 del_u/del_z=del_u/del_r-del_u/del_s-del_u/del_r+del_u/del_s`

`x^2 del_u/del_x+y^2 del_u/del_y+z^2 del_u/del_z=0`

Hence proved.

Concept: .Circular Functions of Complex Number

Is there an error in this question or solution?

Advertisement Remove all ads

#### APPEARS IN

Advertisement Remove all ads

Advertisement Remove all ads